Reinfection With Severe Acute Respiratory Syndrome Coronavirus 2 Without Recurrence of Multisystem Inflammatory Syndrome in Children. Issue 12 (10th August 2021) - Buddingh, Emilie P.; Vossen, Ann C. T. M.; Lamb, Hildo J.; van der Palen, Roel L. F.; Brinkman, Danielle M. C.
Abstract : Multisystem inflammatory syndrome in children is a rare, potentially life-threatening postinfectious complication in children after severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. It is currently unknown if multisystem inflammatory syndrome in children (MIS-C) can recur upon reinfection with SARS-CoV-2. Here, we report on a former MIS-C patient who was reinfected with SARS-CoV-2 without recurrence of MIS-C.